Discovery of N-{4-[(3-Hydroxyphenyl)-3-methylpiperazin-1-yl]methyl-2-methylpropyl}-4-phenoxybenzamide Analogues as Selective Kappa Opioid Receptor Antagonists - Kormos, Chad M. (2013)
There is continuing interest in the discovery and development of new κ opioid receptor antagonists. We recently reported that N-substituted 3-methyl-4-(3-hydroxyphenyl)piperazines were a new class of opioid receptor antagonists. In this study we report the syntheses of two piperazine JDTic-like analogues. Evaluation of the two compounds in an in vitro [(35)S]GTPγS binding assay showed that neither compound showed the high potency and κ opioid receptor selectivity of JDTic. A library of compounds using the core scaffold 21 was synthesized and tested for their ability to inhibit [(35)S]GTPγS binding stimulated by the selective κ opioid agonist U69,593. These studies led to N-[(1S)-1-{[(3S)-4-(3-hydroxyphenyl)-3-methylpiperazin-1-yl]methyl}-2-methylpropyl]-4-phenoxybenzamide (11a), a compound that showed good κ opioid receptor antagonist properties. An SAR study based on 11a provided 28 novel analogues. Evaluation of these 28 compounds in the [(35)S]GTPγS binding assay showed that several of the analogues were potent and selective κ opioid receptor antagonists.